2018
DOI: 10.1371/journal.pgen.1007363
|View full text |Cite
|
Sign up to set email alerts
|

Altered distribution of ATG9A and accumulation of axonal aggregates in neurons from a mouse model of AP-4 deficiency syndrome

Abstract: The hereditary spastic paraplegias (HSP) are a clinically and genetically heterogeneous group of disorders characterized by progressive lower limb spasticity. Mutations in subunits of the heterotetrameric (ε-β4-μ4-σ4) adaptor protein 4 (AP-4) complex cause an autosomal recessive form of complicated HSP referred to as “AP-4 deficiency syndrome”. In addition to lower limb spasticity, this syndrome features intellectual disability, microcephaly, seizures, thin corpus callosum and upper limb spasticity. The pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
132
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(151 citation statements)
references
References 67 publications
18
132
0
1
Order By: Relevance
“…We next examined spinal motor axons and found that morphants exhibited shorter axonal length, indicating that SPG52 may be important for the outgrowth of motor axons. This is consistent with impaired neuron outgrowth found in cultured neurons from Ap4e1 knockout mice 16,17 and similar to results seen in several zebrafish models of HSP including spastin, 18 atl1 , 19 and spatacsin 20 . Seizures are found in about two‐thirds of AP‐4‐HSP patients and febrile seizures are common early in life 3 .…”
Section: Discussionsupporting
confidence: 85%
“…We next examined spinal motor axons and found that morphants exhibited shorter axonal length, indicating that SPG52 may be important for the outgrowth of motor axons. This is consistent with impaired neuron outgrowth found in cultured neurons from Ap4e1 knockout mice 16,17 and similar to results seen in several zebrafish models of HSP including spastin, 18 atl1 , 19 and spatacsin 20 . Seizures are found in about two‐thirds of AP‐4‐HSP patients and febrile seizures are common early in life 3 .…”
Section: Discussionsupporting
confidence: 85%
“…Further, we found slowed SQSTM1/p62 accumulation in KO neurons during these treatments ( Figure 4(j, l); Table S1). Interestingly, steady state levels of LC3 were unaffected in cultured KO neurons (Figure 4(j,k)), but also in hippocampal lysates prepared from animals at 1 month (Figure 4(m,n); relative LC3-II:I ratio: WT 1 ± 0.012, KO 0.82 ± 0.13, p = 0.24; relative LC3-II: WT 1 ± 0.077, KO 1 ± 0.22, p = 0.99; relative LC3-I: WT 1 ± 0.089, KO 1.21 ± 0.14, p = 0.29; t-test), in agreement with data recently reported [30]. Further, we found a robust decrease in SQSTM1/p62 in KO animals at 1 month ( Figure 4(o,p); relative SQSTM1/p62 protein: WT 1 ± 0.11, KO 0.59 ± 0.05, p = 0.025; t-test), similar to that reported in ap4b1 null mice [13].…”
Section: Defective Autophagosome Maturation In Ap4e1 Ko Neuronssupporting
confidence: 92%
“…Similar to our in vivo findings, endogenous ATG9A was increased in KO neurons (Figure 3(a,b); relative neuronal ATG9A signal: WT 1 ± 0.06, KO 2.8 ± 0.2, p < 0.0001; t-test), and other cell types including astrocytes ( Figure S3 (a); relative astrocytic ATG9A signal: WT 1 ± 0.11 KO 2.42 ± 0.27, p < 0.0001; t-test). Given the known localization of AP-4 to the TGN in cell lines, we hypothesized that the sorting of ATG9A may be dependent on AP-4, and thus ATG9A may be retained within the TGN in neurons [26,29,30]. We firstly confirmed neuronal AP-4 localization at the TGN, through staining of endogenous AP4E1 and the TGN resident marker, GOLGA1/ Golgin-97/GOLG97 ( Figure S3(b)).…”
Section: Ap4e1 Null Mice Recapitulate Neuroanatomical Features Of Ap-mentioning
confidence: 74%
“…AP‐4 is composed of four subunits (β4, ε, μ4, σ4) forming an obligate complex and has been shown to be involved in protein trafficking from the trans‐Golgi network to early and late endosomes . Recent studies in cultured cells have demonstrated that the autophagy protein ATG9A is a cargo of AP‐4 and that loss of AP‐4 leads to a mislocalization of ATG9A, potentially impacting the transport and function of ATG9A . Dysregulation of autophagy has been reported in AP‐4 knockout cells and Ap4e1 knockout mice …”
Section: How Rare Monogenic Diseases Teach Us About Autophagy In Neurmentioning
confidence: 99%